Deletion of β-Neurexins in Mice Alters the Distribution of Dense-Core Vesicles in Presynapses of Hippocampal and Cerebellar Neurons - Ferdos, Shima; Brockhaus, Johannes; Missler, Markus; Rohlmann, Astrid (Frontiers in Neuroanatomy, 2022)
Communication between neurons through synapses includes the release of neurotransmitter-containing synaptic vesicles and of neuromodulator-containing dense-core vesicles (DCVs). Neurexins, a polymorphic family of cell surface molecules encoded by three genes in vertebrates (Nrxn1-3), have been proposed as essential presynaptic organizers and as candidates for cell type-specific or even synapse-specific regulation of synaptic vesicle exocytosis. However, it remains unknown whether Nrxn also regulate DCVs. Here we report that at least β-neurexins (βNrxn), an extracellularly smaller Nrxn variant, are involved in the distribution of presynaptic DCVs. We found that conditional deletion of all three βNrxn isoforms in mice by lentivirus-mediated Cre recombinase expression in primary hippocampal neurons reduces the number of ultrastructurally identified DCVs in presynaptic boutons. Consistently, colabeling against marker proteins revealed a diminished population of chromogranin A-positive DCVs in synapses and axons of βNrxn-deficient neurons. Moreover, we validated the impaired DCV distribution in cerebellar brain tissue from constitutive βNrxn knockout (KO) mice, where DCVs are normally abundant and βNrxn isoforms prominently expressed. Finally, we observed that the ultrastructure and marker proteins of the Golgi apparatus, responsible for packaging neuropeptides into DCVs, appear unchanged. In conclusion, based on validation from two deletion strategies in conditional and constitutive KO mice, two neuronal populations from hippocampus and cerebellum, and two experimental protocols in cultured neurons and in brain tissue, this study presented morphological evidence that the number of DCV at synapses is altered in absence of βNrxn. Our results therefore point to an unexpected contribution of βNrxn to the organization of neuropeptide and neuromodulator function, in addition to their more established role in synaptic vesicle release.